Peningkatan Kemampuan Membaca dengan Metode Card Sort pada Mata Pelajaran Bahasa Indonesia di SD Unismuh Makassar - Maria Ulviani; Siti Suwadah Rimang (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: Improving Reading Ability with the Card Sort Method in Indonesian Subjects at SD Unismuh Makassar. Reading is a means for students to learn something that is not yet known and can expand knowledge, students can recognize themselves, their culture even helps to recognize the culture of other people, and students can recognize written messages contained in reading . To achieve the above objectives, it is necessary to have the ability of students to read. The Card Sort method is a learning method that is used to help remember what they have read in reading books, not only from short term memory to long term memory, in fact many students are lazy to read the readings contained in reading books so that students have difficulty understanding the material studied. Based on the results of a pre-survey conducted on December 4 2022 at SD Unismuh Makassar with Indonesian teachers, it is known that problems in learning to read occur in class IV. Students have not been able to read properly and correctly, students have not been able to answer questions related to information and reading material, and draw conclusions from reading. As a result, most students are less active in concluding reading content, students also feel bored with learning to read so they are less enthusiastic about following it. In each reading lesson, the teacher only gives readings and then assigns students to read silently followed by answering questions according to the contents of the reading material. The use of the Card Sort learning method is expected to be able to improve students' reading skills in accordance with the Minimum Completeness Criteria (KKM) for class IV in the Indonesian language subject at SD Unismuh Makassar because, in this Card Sort type cooperative learning method. Students are required to actively carry out the responsibilities of the tasks assigned by the teacher. The results of research using the Card Sort method can improve students' reading skills. Learning with this method can improve the reading of fourth grade students at SD Unismuh Makassar. The average Card Sort method in student learning in Indonesian subjects from the status cycle reached 60.50% then in the second cycle it reached 80.50% so it experienced an increase of 20%. In this case, students' reading increased by 45%. So with an increase in reading, students who complete learning are 80% and students who do not complete learning are 20%.